DIVERSITY AND DOMINANCE OF MANGROVES IN THE WATERS OF AERANO AMAHAI BEACH, AMAHAI DISTRICT, CENTRAL MALUKU REGENCY VAREITY AND DOMINATE IN AMAHAI AERONO BEACH - Laura Mauwa, Silda (PT. Jurnal Center Indonesia Publisher, 2025)
Experiment purpose is to know the kinds, variety and dominance in Amahai Aerono Beach. This experiment was held in February 2017 using cuadran transect with plot size 10 x 10 for tree kind, 5 x 5 for stake kind and 2 x 2 for seedling. Sample identify process in Center Laboratory of DEEP Sea Experiment (LIPI Ambon). Species variety is a community characteristic based on biological organization, while dominance is the parameter proving the species dominates in a community. In experiments found 7 kinds of mangroves, Rhizophora apiculata, Ceriops tagal, Bruguiera gymnorrhiza, Sonneratia alba, Aegiceras corniculatum, Bruguiera parviflora, and Avicennia officinalis. Included in lowly dominate and have medium characteristics.